1998
DOI: 10.1038/sj.onc.1201623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a BRCA1-associated kinase with potential biological relevance

Abstract: A biochemical approach was used to identify proteins which interact with human BRCA1. Through this work, a kinase activity which co-puri®es with BRCA1 has been identi®ed. This kinase activity, which phosphorylates BRCA1 in vitro, was originally identi®ed in Sf9 insect cells but is also present in cells of human origin including breast and ovarian carcinoma cell lines. The BRCA1 kinase activity in vitro is associated with a fragment of BRCA1 encompassing amino acids 329 ± 435. This peptide is also phosphorylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, our previous studies revealed that BRCA1 is predominantly phosphorylated on serine and threonine residues, at least in the cell lines analyzed (57). Furthermore, a kinase activity that associates with and phosphorylates a BRCA1 fragment containing aa 329 to 435 in vitro was identified (9).…”
Section: Discussionmentioning
confidence: 93%
“…However, our previous studies revealed that BRCA1 is predominantly phosphorylated on serine and threonine residues, at least in the cell lines analyzed (57). Furthermore, a kinase activity that associates with and phosphorylates a BRCA1 fragment containing aa 329 to 435 in vitro was identified (9).…”
Section: Discussionmentioning
confidence: 93%
“…The following mutagenic primers were used: 5 -C ACA CGA GGG CAG CCT GTC CTC GAG CCA CCA GAT CAG CTG GTC-3 (for αT638E); 5 -C CAG TCT GAT TTT GAA GGG TTC GAA TAT GTC AAC CCC CAG TTT GTG C-3 (for αT657E); 5 -C GAT GAG GTT CTT GTC ACT GAA CTC GAG TTG GGG TTT CTC ATT CAG G-3 (for δS643E); 5 -G CTC ATA TTT GGG GTT CAC GAA TTC GAA GCC CTT GAA GGC TGT CTG G-3 (for δS662E). GFP-tagged deletion mutants of PKCα and PKCδ lacking the C1A or C1B domain were constructed using QuikChange II XL Site-Directed Mutagenesis Kit (Stratagene) [26] with PKCα-GFP or PKCδ-GFP as a template. The primers used for the deletion were as follows: 5 -G AAG AAC GTG CAT GAG GTG AAA GAC CCG GGT GCG GAT AAG GGA CCT GAC-3 and 5 -GTC AGG TCC CTT ATC CGC ACC CGG GTC TTT CAC CTC ATG CAC GTT CTT C-3 (for αC1A); 5 -GAC ACT GAT GAC CCC AGA AGC AAG GGA ATG GAT CAC ACA GAG AAG AGG-3 and 5 -CCT CTT CTC TGT GTG ATC CAT TCC CTT GCT TCT GGG GTC ATC AGT GTC-3 (for αC1B); 5 -GCC AAG ATT CAC TAC ATC AAG AAC ACT GGC ACT GCT ACC AAT AGC CGG G-3 and 5 -C CCG GCT ATT GGT AGC AGT GCC AGT GTT CTT GAT GTA GTG AAT CTT GGC-3 (for δC1A).…”
Section: Plasmid Constractsmentioning
confidence: 99%
“…Although the molecular function of BRCA1 is controversial and may include DNA repair or transcriptional functions [13], overexpression of BRCA1 into sporadic breast or ovarian cancer cells, which usually show low BRCA1 expression [14], results in growth inhibition and tumor suppression [15,16,17,18,19,20,21,22,23]. Growth inhibition by BRCA1 has itself been controversial, leading some to question the rationale for BRCA1 gene therapy [24], but subsequent studies have shown growth inhibition or tumor suppression by BRCA1 in vitro [16,17,19,20,21,22,23] and in vivo [15,17,21,25].…”
Section: Brca1 Gene Therapymentioning
confidence: 99%
“…Growth inhibition by BRCA1 has itself been controversial, leading some to question the rationale for BRCA1 gene therapy [24], but subsequent studies have shown growth inhibition or tumor suppression by BRCA1 in vitro [16,17,19,20,21,22,23] and in vivo [15,17,21,25]. The mechanism of growth inhibition by BRCA1 is unknown and may involve interactions with WAF1/CIP1 [16], p53 [17], Rb [23] or induction of apoptosis [18,19].…”
Section: Brca1 Gene Therapymentioning
confidence: 99%